Strategi Inovatif Home Industry Kasba Makmur dalam Pemberdayaan Perempuan Pekerja Pengupas Rajungan - Dini, Alya Muflihatud (Islamic Management and Empowerment Journal, 2023)
The existence of the crab peeling home industry is not only about creating job opportunities for women, but also providing them with a platform to develop economic skills. This research aims to understand the strategies implemented by Kasba Makmur's home industry in an effort to improve women's economic welfare through crab shelling. By focusing on crab peeling workers, this can be a source of empowerment for local women, both from an economic perspective and other aspects related to individual welfare. . This research uses a descriptive qualitative method with data collection techniques through observation, semi-structured interviews with research informants selected using purposive sampling techniques, and is supported by documentation and relevant literature studies. Data analysis uses interactive analysis miles and huberman. The results of this research show that through planned strategies, such as focusing on recruiting women in coastal areas from Mlaten Village, providing training that increases capacity, and empowering women in coastal areas through awareness, capacity building and empowerment stages, Home Industry Kasba Makmur not only creates jobs for local communities, but also play a key role in advancing the role of women in local economic activities.